The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.brainres.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly in aortic arch alters pathological outcome of transient global ischemia in Rhesus macaques

Abstract: We investigated a non-human primate (NHP) transient global ischemia (TGI) model which was induced by clipping the arteries originating from the aortic arch. Previously we demonstrated that our TGI model in adult Rhesus macaques (Macaca mulatta) results in marked neuronal cell loss in the hippocampal region, specifically the cornu Ammonis (CA1) region. However, we observed varying degrees of hippocampal cell loss among animals. Here, we report for the first time an anomaly of the aortic arch in some Rhesus maca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, ischemic damage of the white matter is a prognostic factor for stroke outcomes. However, only NHP stroke models are able to mimic white matter pathology in stroke patients most closely to pathology seen in humans and is recognized as an important limitation to rodent ischemic stroke models [20][21][22][23][24]. Thus, NHP stroke models have numerous intrinsic advantages over rodents, especially owing to their similarity in different fronts of the human anatomy and physiology, making them an irreplaceable and indispensable animal model for studying cerebral ischemia [25].…”
Section: Ischemia Models In Nhpsmentioning
confidence: 99%
“…Moreover, ischemic damage of the white matter is a prognostic factor for stroke outcomes. However, only NHP stroke models are able to mimic white matter pathology in stroke patients most closely to pathology seen in humans and is recognized as an important limitation to rodent ischemic stroke models [20][21][22][23][24]. Thus, NHP stroke models have numerous intrinsic advantages over rodents, especially owing to their similarity in different fronts of the human anatomy and physiology, making them an irreplaceable and indispensable animal model for studying cerebral ischemia [25].…”
Section: Ischemia Models In Nhpsmentioning
confidence: 99%
“…An experimental study conducted by Hara et al (), with adult rhesus monkeys ( Macaca mulatta ), showed the degree of impairment of the nervous tissue, specifically the loss of hippocampal cells in relation to the blood supply by the collateral arteries to the aortic arch. Through histological analyses using the Nissl staining, they verified that animals with two of the three connected arterial branches that were clamped had a partial loss of cells and minimal alteration in the number of cell layers in the hippocampal region when compared to clamping of the three branches, resulting in cell death of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo realizado com macacos Rhesus adultos [16], para avaliar o grau de comprometimento do tecido nervoso, especificamente à perda das células do hipocampo, induzido por clipagem das artérias oriundas do arco aórtico cirurgicamente no tempo de 10 a 15 min, resultando assim na isquemia transitória do tecido, no entanto, durante o experimento observaram por acaso que 30% dos animais apresentaram três artérias colaterais no arco aórtico (tronco braquiocefálico, carótida comum esquerda e subclávia esquerda) ao invés de duas (tronco braquiocefálico e subclávia esquerda). Inicialmente tinham a intenção de clipar as únicas duas artérias colaterais do arco, e no momento que descobriram que existiam animais que possuíam as três artérias, compararam a perda de células do hipocampo entre os animais com 3 ramos arteriais, mas que tiveram todos ou apenas dois ramos cortados durante a operação.…”
Section: Discussionunclassified